POSITRON EMISSION TOMOGRAPHY IN GYNECOLOGIC ONCOLOGY - D. V. Ryzhkova; V. L. Vinokurov; V. S. Pavlova; M. V. Rogachev (Сибирский онкологический журнал)
The literature review is devoted to the analysis of radiopharmaceutical agents and the efficiency of positron emission tomography (PET) for diagnosis, evaluation of tumor spread and assessment of treatment response in patients with gynecological cancer. Diagnostic value of PET using18F-fluorodeoxyglucose was demonstrated in the diagnosis of primary tumor, assessment of the extent of tumor involvement and treatment response in patients with cancer of the cervix and body of the uterus, ovaries and vulva.